GROSS PATHOLOGY, BLOOD CHEMISTRY, LIPID AND PEROXIDE CONTENTS IN RAINBOW TROUT (ONCORHYNCHUS MYKISS WALBAUM) AFFECTED BY EXPERIMENTAL ARCOBACTER CRYAEROPHILUS INFECTION AT LOW WATER TEMPERATURE - Aydın, Seyit; Güre, Hayati; Çakıcı, Hasan; Çolakoğlu, Serhat; Bircan, Recep (Acta Veterinaria Hungarica 57 (2), pp. 305–317 (2009), 2009)
(Oncorhynchus mykiss Walbaum), and its pathogenicity was tested by intramuscular injection using healthy 1-year-old rainbow trout under cold-water conditions (at 5 °C). The lethal dosage of 50% end point (LD50) for A. cryaerophilus was calculated as 7.79 × 105 viable cells. Experimental infection caused gross clinical abnormalities such as fallen scales, exophthalmia, oedema in injection region and at the base of fins, pale gills, kidney necrosis, hyperaemic areas in pale liver, haemorrhagic spots in heart, elongated spleen and swollen gallbladder. Activities of aspartate aminotransferase and alkaline phosphatase, and concentrations of glucose, total protein, albumin, cholesterol, triglyceride and calcium in the serum of the experimentally infected rainbow trout were significantly decreased compared with the healthy fish. Positive correlations were observed among blood parameters. Total lipid weights increased in the brain, muscle and liver tissues of infected fish and dropped in the gill and spleen tissues. Lipid peroxide contents in the brain, liver, kidney, spleen, muscle and gill tissues of infected rainbow trout were significantly higher than in healthy animals. The present work shows that A. cryaerophilus can be moderately virulent for rainbow trout at low water temperature, and changes in lipid and lipid peroxide contents of tissues and blood indices can highlight barely detectable effects of A. cryaerophilus infection in rainbow trout under laboratory conditions. However, the application of these indices in farm biomonitoring using rainbow trout will need more detailed studies and a careful consideration of the environmental parameters.
Keywords: Arcobacter cryaerophilus, disease, pathogenicity, rainbow trout, blood, enzyme, metabolite, electrolyte, lipid, peroxide, temperature